Teacher Education as a Profession : In Search of Quality Teacher - Suharno Suharno (Universitas PGRI Semarang, 2010)
Abstract For the last 50 years educators have spent a great deal of energy and time to the debate over whether teaching can be classified as a profession.?é?á This paper aims to elaborate the issues of teacher education as a profession and the attempts of classifying characteristics of quality teachers. Teacher education itself is intended to improve the teacher?óÔé¼Ôäós skills and knowledge and there have been some approaches for the teacher development such as teacher-as-researcher, action research, clinical supervision, reflective teaching, etc. From the teacher education or development we can figure out some features of effective or quality teachers. ?é?á Key words: teacher education, profession, quality teacher, approach, research